A Low-Cost Diffraction-based Light Wavelength Measurement for Classroom Purposes - Eka Cahya Prima; A Z Y Muntaz; F Muslihah; G S A Muharam; L A Kurniawan; M F Ulfi; W T Saputra (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2023)
As requested by science education curricula, students are challenged to analyze light properties through optical instruments. However, the light is an electromagnetic wave, and it is very short and not easy to be measured using conventional instruments like a vernier caliper. The research aims to measure light wavelength by analyzing the light diffraction phenomenon for classroom purposes. The method applied Huygens's diffraction principle. The parameters used for the independent variable are the types of lasers and the gap between the laser and screens. Next, the dependent variables are the diffraction angle, wavelength (?), and the gap between diffraction spots. We used diffraction slits (2,500 and 7,500 lines per inch) as control variables. Three laser beams passing through the various slits can be seen and further evaluated to estimate the wavelength. The result shows that the lasers with different wavelengths (665.45, 544.35, 416.20 nm) have been demonstrated successfully with percent errors of 2.32-2.76% and percent differences of 2.29-2.73%. We have concluded that this low-cost experiment can be implemented in school.